Bioecologia de Paralonchurus brasiliensis (Steindachner, 1875) capturados na pesca artesanal de arrasto de Xiphopenaeus kroyeri (Heller, 1862), Penha, Santa Catarina, Brasil - Sedrez, Mário Cesar (Universidade Federal de São Carlos, 2017)
This thesis describes the bio-ecology of Paralonchurus brasiliensis caught as bycatch for the shrimp trawling fishery targeting Xiphopenaeus kroyeri in Penha, Brazil. Series of 30 minute trawls were made between July/2013 and June/2014 at depths of 10, 20 and 30 meters during which 3040 specimens of P. brasiliensis were collected. All specimens were weighed(g) and measured total length (TL in cm) and from a subsample of 1219 specimens data was obtained for sex-ratio, gonad weight, gonadal maturity, stomach repletion and diet. Paralonchurus brasiliensis is abundant and very frequent, in the bycatch of X. kroyeri, with a ratio of approximately 1: 1 kg between its average biomass and that of the targeted shrimp. CPUE both in number and biomass/trawling did not suffer significant variations and there was no population stratification among the isobaths. In the captures, a large amplitude of Lt (2.7- 23.3cm) was obtained, with a higher number of juveniles and females, regardless of depth. Asymptotic length (L∞) was estimated for males at 33.6 cm, females (30.4 cm) and size of first gonadal maturation estimated for males (16.4cm) and females (15.8 cm). The closed period of shrimp trawling for X. kroyeri only protects the early stages of P. brasiliensis, a continuous yearlong breeding species with peaks between autumn (may) and spring (october). There were significant correlations between abundance versus sand and silt, biomass vs. bottom temperature and silt, as well as RGS-M vs. Silt. The positive allometric growth and relative condition factor close to 1.0 (kn=1), indicated a favorable physiological condition of the specie in the three isobaths. This species showed intense foraging activity, evidenced by the high percentage of stomachs with food (95.73%). The diet of P. brasiliensis is diversified, with greater consumption of polychaetes, crustaceans and ophiuroids, which enables us to classify it as a carnivorous species, predominantly invertivorous. Paralonchurus brasiliensis is a key benthic-demersal species and an opportunistic predator over a wide trophic range intersecting with a vast number of macro-benthic species on marine coastal food webs along the South Brazilian shorelines. Besides the characterization important bioecological aspects of P. brasiliensis, this work contributes to the discussion and understanding of the impact of trawling at the local and world level using the case of P. brasiliensis as a study model.
Keywords: Pesca marinha; Pesca extrativa; Pesca de arrasto; Estrutura populacional; Ecologia trófica; Marine fishing; Extraction fishery; Trawl fisheries; Population structure; Trophic ecology; CIENCIAS BIOLOGICAS::ECOLOGIA